Sistem Informasi Rekam Medis Kedokteran Gigi Berbasis Website - Kelvin Christianto; Kristo Radion Purba; Agustinus Noertjahyana (Jurnal Infra, 2017)
At this time many doctors appointment was made by telephone and it is less effective and practical. On the other hand there are many medical record dentistry is done manually. Entry data which is done manually often waste of time because the nurses had to find the archive file a particular patient's medical record. Additionaly, patients often lost or hard to find.Looking at the various problems that occurred from appointment to the medical record on the patient, this software is a system that can process  patient appointment data, and also record the patient's medical history. This software is created with the web-based program that uses PHP and MySQL as the database.The end result of this program is that users can perform an online appointment at a doctor's office specified in according with the schedule. Besides that, doctors can make record medical record online and history can be viewed online.